Prediction of pathological complete response after neoadjuvant chemotherapy for HER2-negative breast cancer patients with routine immunohistochemical markers - Häberle, Lothar; Erber, Ramona; Gass, Paul; Hein, Alexander; Niklos, Melitta; Volz, Bernhard; Hack, Carolin C.; Schulz-Wendtland, Rüdiger; Huebner, Hanna; Goossens, Chloë; Christgen, Matthias; Dörk, Thilo; et al. (Breast cancer research, 2025)
Pathological complete response (pCR) is an established surrogate marker for prognosis in patients with breast cancer (BC) after neoadjuvant chemotherapy. Individualized pCR prediction based on clinical information available at biopsy, particularly immunohistochemical (IHC) markers, may help identify patients who could benefit from preoperative chemotherapy.